Exploration of racial integration of learners into selected schools in the Limpopo Province - Maraba, Maria Mokgaetjie Dorah (My University, 2006)
The education sector in South Africa is in a process of transformation and learners attend schools of choice. Currently, educational statutes prohibit discrimination in any form in schools. The Constitution of the Republic of South Africa (Act no 108 of 1996) gives everyone the right to basic education without being discriminated against by the management of any school. The South African Schools (Act No 84 of 1996) that ensures equal education for all learners further advances this basic right. This has therefore encouraged parents to enroll children in schools of their choice. Racial integration is a way of life that promotes multiculturalism and diversity of the entire society and schools in particular. An exploration study was conducted with the aim of exploring to what extent integration has been realised among learners in selected multiracial public schools in the Limpopo Province. The snowball sampling method in the form of interviews was used in this study. Teachers and learners participated in this interview process. The observation method was also used in data collection. The study was motivated by the researcher’s observation of conflicts among learners from different racial backgrounds attending multiracial schools. These conflicts have been constantly reported in the media. In most cases, such conflicts are racially motivated and schools experience problems in handling and managing such conflicts. The results of this study show that most learners who participated in the interview process are positive towards integration. They indicated that they learn more about cultural diversity. However, some white learners still have a problem of integrating with black learners. Parents, who are not willing to accept change in this country, at times fail to motivate their children to accept and understand other racial groups. Most white learners leave such schools to attend Afrikaansonly or private whites-only schools in order to avoid being racially integrated into v multiracial public schools. During data collection, it was revealed that the problem in some schools is compounded by lack of tolerance among members of the teaching staff who come from different racial and cultural backgrounds. This study recommended among others, that more workshops on cultural diversity should be conducted on a continuous basis to assist both teachers and learners to understand and accept one another better. Furthermore, schools should develop integration programmes that will motivate everyone to understand different racial groups. Through these programmes it is hoped that schools will be assisted to overcome their differences and conflicts will be minimized. All racial groups will be united and transformation in the education sector will be promoted. White learners leaving multiracial schools will be motivated and encouraged to understand different racial groups who live in this democratic country.
Thesis (MDev.) --Univesity of Limpopo, 2006
Keywords: multiracial public schools; integration; conflicts; transformation